Diversity awareness perceptions among classified staff at a Midwestern Land Grant University - Grice, Cheryl Denise-Roshell (Kansas State University, 2011)
Diversity is recognized by acknowledging individual differences. The term diversity can refer to an array of descriptors such as, race, religion, color, gender, national origin, disabilities, sexual orientation, age, level of education, geographic origin, economic status, family status, appearance/physical size and skill characteristics. Although there are multiple definitions of diversity, many include at least one or all of the attributes listed above. This qualitative study examined perceptions of classified employees regarding the level of diversity awareness among their workforce at a large Midwestern land grant university. The sample was purposefully selected from the population of classified support staff using both scores from Dahm’s (2006) Organizational Diversity Needs Analysis (ODNA) and responses to demographic questions. This survey was designed to measure diversity awareness in the workplace using the dimensions; cultural inclusion or exclusion, organizational inclusion or exclusion, workload, trust, sensitivity and affirmative action. Demographic information used to select the sample for this study included; age (Generation Y, Generation X and Baby Boomers), gender (male and female), and race and ethnicity (White and all others, for example: African American, Asian American, Hispanic and Native American). Semi-formal, one-on-one interviews were conducted with the participants by the researcher in this study. Additionally a theme emerged that expressed the “good old boy” system as being “alive and well”; differential treatment among staff who did not have the same or similar levels of education; positional power and situational occurrences whereby individuals who appeared different were treated unfairly or without respect by other staff, faculty or students at the university. Findings included a difference in perceptions about diversity awareness between Whites and non Whites. Whites fell into the following categories; 1) Many employees felt the current status of diversity awareness was sufficient, 2) an equal number of others felt that their needed to be an increase in diversity awareness initiatives among employees, 3) others felt as though diversity awareness was problematic or 4) the need did not exist for diversity awareness initiatives. Non White participants disagreed, all claimed to have been the victim of discriminatory behavior.
Keywords: Diversity Awareness Perceptions University Classified Staff; Public Administration (0617)